Chronic GIPR agonism results in pancreatic islet GIPR functional desensitisation - Iona Davies; Alice E. Adriaenssens; William R. Scott; David Carling; Kevin G. Murphy; James S. Minnion; Stephen R. Bloom; Ben Jones; Tricia M-M. Tan (Molecular Metabolism)
Objectives: There is renewed interest in targeting the glucose-dependent insulinotropic polypeptide receptor (GIPR) for treatment of obesity and type 2 diabetes. G-protein coupled receptor desensitisation is suggested to reduce the long-term efficacy of glucagon-like-peptide 1 receptor (GLP-1R) agonists and may similarly affect the efficacy of GIPR agonists. We explored the extent of pancreatic GIPR functional desensitisation with sustained agonist exposure. Methods: A long-acting GIPR agonist, GIP108, was used to probe the effect of sustained agonist exposure on cAMP responses in dispersed pancreatic islets using live cell imaging, with rechallenge cAMP responses after prior agonist treatment used to quantify functional desensitisation. Receptor internalisation and β-arrestin-2 activation were investigated in vitro using imaging-based assays. Pancreatic mouse GIPR desensitisation was assessed in vivo via intraperitoneal glucose tolerance testing. Results: GIP108 treatment led to weight loss and improved glucose homeostasis in mice. Prolonged exposure to GIPR agonists produced homologous functional GIPR desensitisation in isolated islets. GIP108 pre-treatment in vivo also reduced the subsequent anti-hyperglycaemic response to GIP re-challenge. GIPR showed minimal agonist-induced internalisation or β-arrestin-2 activation. Conclusions: Although GIP108 chronic treatment improved glucose tolerance, it also resulted in partial desensitisation of the pancreatic islet GIPR. This suggests that ligands with reduced desensitisation tendency might lead to improved in vivo efficacy. Understanding whether pancreatic GIPR desensitisation affects the long-term benefits of GIPR agonists in humans is vital to design effective metabolic pharmacotherapies.